Behavioral response of Biomphalaria glabrata exposed to a sublethal concentration of Euphorbia milii var. hislopii latex - Silva, Anna Carla Alberto (2020)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Avaliação e Promoção da Saúde Ambiental. Rio de Janeiro, RJ, Brasil / Universidade Federal Rural do Rio de Janeiro, Instituto de Veterinária. Curso de Pós-Graduação em Ciências Veterinárias. Seropédica, RJ, Brasil.